KoGuRuPa: Kolaborasi Guru, Orang Tua dan Pengasuh untuk Mewujudkan Kota Surabaya Layak Anak - Putri, Rizca Yunike; Herbowo, Heru Dwi; Musrifah, Sri; Choiriyah, Septiana Syahra; Purwati, Enik; Halizah, Caroline Nur; Mufidah, Ainun Tafsil; Siva, Bayu Raka Bayu Cahyarie (LPPI UMN AL WASHLIYAH, 2024)
Surabaya as an administrative city in realizing the Regulation of the Ministry of Women's Empowerment and Protection (PPPA) Number 12 carries out implementation with the Child-Friendly Village program which has been effectively running since 2021. This program is a derivative of the Surabaya City Regulation Policy Number 6 of 2011 concerning the Implementation of Child Protection and has a task force in each district to control the implementation of the program, coordinate with district institutions and schools in the suburbs area. Early Childhood Education has its own challenges in carrying out these 3 functions. Especially in the era of millennial and Gen-Z parents who are open-minded, choose professional careers, and entrust their children to school institutions not only for education but also for care. Schools with educational program facilities as well as care are not free from the potential for violence against children. Violence that occurs to children is not only bullying behavior carried out by their peers, but also by schools, caregivers, families and even relatives. Education and personal safety provided to early childhood in the city of Surabaya can be done through collaboration between schools, guardians and caregivers, known as the Teacher, Parent and Caregiver Collaboration Program (KoGuRuPa).